2011
DOI: 10.3143/geriatrics.48.176
|View full text |Cite
|
Sign up to set email alerts
|

A case of obturator hernia with overlooked Howship-Romberg sign and treated as sciatica

Abstract: We report a case of a patient with incarcerated obturator hernia who presented with right thigh pain. An 88-year-old woman who had experienced right thigh pain for the previous 3 years was given a diagnosis of sciatica at the orthopedic department. In July 2009, she was hospitalized with the chief complaint of appetite loss. The day after admission she experienced increased right thigh pain and lower abdominal pain. Abdominal ultrasonography revealed a keyboard sign. Based on this finding, we diagnosed an ileu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Obturator hernias are difficult to diagnose and 80% of patients present with small bowel obstruction symptoms in the form of crampy abdominal pain that can be vague some times, with nausea and vomiting [6]. Symptoms confusing with sciatica has been reported [7]. While flexion of the thigh usually relieves pain in patients with obturator hernia, it has not been reported as a presenting symptom as we describe in our case.…”
Section: Discussionmentioning
confidence: 68%
“…Obturator hernias are difficult to diagnose and 80% of patients present with small bowel obstruction symptoms in the form of crampy abdominal pain that can be vague some times, with nausea and vomiting [6]. Symptoms confusing with sciatica has been reported [7]. While flexion of the thigh usually relieves pain in patients with obturator hernia, it has not been reported as a presenting symptom as we describe in our case.…”
Section: Discussionmentioning
confidence: 68%
“…Although obturator hernia is relatively insidious, Howhip-Romberg sign is still important in the diagnosis of IOH, which is an indication of obturator nerve irritation resulting in pain radiates from the inner thigh to the knee, accounting for 37% to 60% of all patients. [11][12][13][14] In fact, CT examination is widely used for the diagnosis of IOH with an accuracy of over 90%, which is also considered the gold standard for diagnosis. 11,15,16 CT scan demonstrated incarcerated small bowel in obturator region with signs of proximal intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as a pain in the lower limbs caused by compression of the obturator nerve by the hernia in the obturator canal. Some studies have reported that the Howship-Romberg sign is seen in 37% to 60% of cases [68]. However, OH tends to develop in thin, aged women, who cannot describe their symptoms due to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers reported that the mortality for complicated OH was 12–70% [11]. Thus, in principle, essentially all patients must undergo surgery, whether laparotomy or a laparoscopic operation [6]. Furthermore, many patients undergo surgery to prevent the recurrence of OH.…”
Section: Discussionmentioning
confidence: 99%